Diabetes: A risk factor for periodontitis - Shaju JACOB; Sonia NATH; Muthu ARUNCHALAM (International Arab Journal of Dentistry (IAJD), 2012)
Severe periodontitis is the major reason for tooth loss in adults. Diabetes is one of the major risk factor for progression of periodontitis. Over 200 articles have been published in the English literature in the past 50 years examining the relationship between these two chronic diseases. The purpose of this review is to provide the reader with practical knowledge concerning the relationship between diabetes mellitus and periodontal diseases. Pubmed and medInd were searched and suitable publications were reviewed. Data interpretation is often confounded by varying definitions of diabetes and periodontitis and different clinical criteria applied to prevalence, extent, and severity of periodontal diseases, levels of glycemic control, and complications associated with diabetes.